2019
DOI: 10.1103/physrevd.99.036020
|View full text |Cite
|
Sign up to set email alerts
|

Schwinger pair production and string breaking in non-Abelian gauge theory from real-time lattice improved Hamiltonians

Abstract: Far-from-equilibrium dynamics of SU (2) gauge theory with Wilson fermions is studied in 1 + 1 space-time dimensions using a real-time lattice approach. Lattice improved Hamiltonians are shown to be very efficient in simulating Schwinger pair creation and emergent phenomena such as plasma oscillations. As a consequence, significantly smaller lattices can be employed to approach continuum physics in the infinite-volume limit as compared to unimproved implementations. This allows us to compute also higher-order c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…This mechanism is known as string breaking and has been investigated extensively from a static point of view [4][5][6][7][8][9][10][11]. Recently, however, its dynamics has gained increased attention [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Importantly, many aspects of confinement cannot only be realized in gauge theories, but also in conventional quantum spin chains [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is known as string breaking and has been investigated extensively from a static point of view [4][5][6][7][8][9][10][11]. Recently, however, its dynamics has gained increased attention [12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Importantly, many aspects of confinement cannot only be realized in gauge theories, but also in conventional quantum spin chains [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…At this stage we have a finite basis in which to work. Working in the BLFQ basis jαi we can diagonalize the Hamiltonian in order to find the QED eigenstates jβi and eigenvalues P − β satisfying the time-independent Schrödinger equation (9). [It is straightforward to obtain the matrix elements in the BLFQ basis by using the commutation relations of the creation and annihilation operators of the Fock states; see the Appendix, Eq.…”
Section: B Basis Light-front Quantizationmentioning
confidence: 99%
“…The lattice is a well-known example, and real-time lattice techniques can now be used to analyze e.g. string breaking and the Schwinger effect [9]. Within laser-plasma physics, a common tool is the simulation of processes using particle-in-cell (PIC) codes, in which Monte Carlo routines based on QED calculations are included to simulate (tree level) quantum effects; for a review see [10].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the great progress in experiments, the realtime dynamics of LGTs has attracted enormous attentions recently. These include the glassy dynamics of the many-body localization state induced by superselection of gauge sectors [38][39][40], the fermion production and string breaking in cold atom simulators [41][42][43][44], and the dynamical phase transitions after a sudden quench in the Schwinger model [45,46]. However, it was shown that the number of the topological defects may not satisfy the usual KZM in some local gauge invariant systems due to the gauge field fluctuation [47,48].…”
Section: Introductionmentioning
confidence: 99%